Ombudsman's experience in Psychosocial Care Centers for alcohol/drugs - Marina Nolli Bittencourt; Diúlia Cristina Pantoja de Oliveira; Ruan Patrick de Oliveira Souza; José Luís da Cunha Pena; Paulo Victor das Neves Pantoja; Maria Odete Pereira
ABSTRACT Objective: The objective of the study was to analyze criticisms, compliments and suggestions of users, family and workers, placed in an Ombudsman of a Centro de Atenção Psicossocial para Álcool e outras Drogas (Psychosocial Care Centers for Alcohol and Other Drugs- CAPS ad). Method: A study carried out in the CAPS ad of Macapá-AP from August to December 2016, through the thematic content analysis of the files deposited in the ombudsman, recently introduced in the service, containing criticisms, compliments and suggestions from users, family members, and CAPS ad. Results: It was observed the dissatisfaction with the infrastructure of the CAPS ad, and with the relationships built between users and professionals, in addition, suggestions were given of workshops, and improvement in the development of the Projeto Terapêutico Singular (freely translated as Unique Therapeutic Project). Final considerations: It is concluded that the multidisciplinary team needs to put in practice the real psychosocial care in the service, and that the management helps in the improvement of the service's place, and in the proposal of qualifications to this team.